2006
DOI: 10.1590/s0034-70942006000500005
|View full text |Cite
|
Sign up to set email alerts
|

Validade da escala hospitalar de ansiedade e depressão em pacientes com dor crônica

Abstract: JUSTIFICATIVA E OBJETIVOS:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
24

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 11 publications
3
35
0
24
Order By: Relevance
“…Several studies have found that the former had good sensitivity, specificity and internal consistency to assess symptoms of anxiety and depression [20][21][22][23] .…”
Section: Hospital Anxiety and Depression Scale (Had)mentioning
confidence: 99%
“…Several studies have found that the former had good sensitivity, specificity and internal consistency to assess symptoms of anxiety and depression [20][21][22][23] .…”
Section: Hospital Anxiety and Depression Scale (Had)mentioning
confidence: 99%
“…Para verificar a presença de sintomas depressivos nos pacientes, valeu-se da Escala Hospitalar de Ansiedade e Depressão (HADS), adaptada à população brasileira por Botega, Bio, Zomignani, Garcia e Pereira (1995) e Castro et al (2006). Essa escala possui 14 itens, dos quais sete são voltados para a avaliação da ansiedade (HADS-A) e sete para a depressão (HADS-D), apresentando os respectivos coeficientes de alfa de Cronbach, 0,68 e 0,77, cada item pode ser pontuado de zero a três, compondo uma pontuação de 0± 21 (Marcolino et al, 2007;Botega et al, 1995).…”
Section: Introductionunclassified
“…Treating these patients constitutes a challenging and often frustrating task for the agents involved. It is noteworthy that the stress levels of caregivers are influenced by the reactions of the patients, who may present depression or anxiety (3) before treatments that induce many collateral effects with little immediate relief of suffering (2,4) . Added to this is the overload of work and the difficulties caused by their participation in a team composed of professionals of heterogeneous training (5)(6) .…”
Section: Introductionmentioning
confidence: 99%